Pengaruh Pemasaran Konten dan Reputasi Kampus terhadap minat berkuliah di UC Makassar - Andi Muhammad Budiman; Antonius Giovanni Lirungan; Gilbert Alvaro; Jonathan Andrew Hartono; Vincent Ciuwanto; Cipta Canggih Perdana (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2025)
This research aims to analyze the influence of content marketing and campus reputation on interest in studying at Ciputra University, Makassar. With increasing competition in the higher education sector, content marketing has become an important strategy to attract prospective students. The college's reputation also plays a crucial role in their decision. This research uses quantitative methods by distributing questionnaires to 200 respondents who are prospective students. Data analysis was carried out using multiple linear regression to test the relationship between content marketing variables, campus reputation, and interest in studying. The research results show that both content marketing and campus reputation have a positive and significant influence on interest in studying. These findings provide insight for campuses in developing effective marketing strategies to increase the attractiveness and image of the institution.